weSPOT: A Personal and Social Approach to Inquiry-Based Learning - Protopsaltis, Aristidis; Hetzner, Sonia; et al. (Journal of Universal Computer Science, 2013)
weSPOT is a new European initiative proposing a novel approach for personal and social inquiry-based learning in secondary and higher education. weSPOT aims at enabling students to create their mash-ups out of cloud-based tools and services in order to perform scientific investigations. Students will also be able to share their inquiry accomplishments in social networks and receive feedback from the learning environment and their peers. This paper presents the research framework of the weSPOT project, as well as the initial inquiry-based learning scenarios that will be piloted by the project in real-life educational settings.
Keywords: social learning; scientific inquiry; personal learning environment; cloud learning environment; inquiry-based learning